Use of the Virtual Reality Environment to Improve the Self-efficacy of Faculty Members in the Production of Electronic Courses - Almandeel, Kholod Khaled (Journal of Educational and Psychological Sciences, 2020)
The study is amid to evaluate the impact of virtual blackboard Environment in optimizing the quality and skills of the staff of Majmaah University, in order to develop the e- curriculums, and their satisfaction of Virtual Blackboard. The researcher has applied the quasi-experimental design which based on individual group, to evaluate the impact of virtual blackboard Environment in optimizing the quality and skills of the staff. The researcher has also applied the descriptive approach to measure staff satisfaction on the virtual blackboard Environment. A purposive sample was selected which comprised (25) university staff of Majmaah. The sample of study of staff has been trained to develop e-curriculums. The study was conducted within two questionnaires; the first one was dedicated to measure the impact of in optimizing the quality and skills of developing the e-curriculums; the second one was dedicated to evaluate the satisfaction of the staff of applying Virtual Blackboard Environment. Consequently, the study tools and treatment have been conducted, and the results indicated that there were statistically significant of Virtual Blackboard Environment in optimizing the quality and skills of developing the Virtual Blackboard environment within the study sample. The results also indicated that there was significant satisfaction of applying the Virtual Blackboard environment within the study sample in developing the e-curriculums. The satisfaction average was reached to (2.55) and (78%). The researcher proposed appropriate recommendations including stimulation of the staff within the universities to develop the e-curriculums and progressing it, which tends to optimize the quality and skills of the staff in this scope.
Keywords: Electronic courses; self-efficiently; Blackboard